Propuesta para la implementación del Sistema de Gestión Integrado ISO 9001:2008 e ISO 17025:2005 en el Laboratorio de Producción de la Escuela Colombiana de Ingeniería Julio Garavito (2015)
Through the present work of degree a proposal is developed that establishes the criteria to implement an Integrated Management System taking as reference the norms NTC-ISO 9001: 2008 and NTC-ISO / IEC 17025, this last norm is focused to demonstrate the competences laboratory techniques. Given the above, the importance of supporting the management carried out by the Production Laboratory in all its areas of work and of contributing to the achievement of one of the purposes contemplated in the 2010-2020 development plan "Achieve recognition, accreditation and certification National and international". For the development of the proposal, the pertinent stages for the implementation of the SGI were defined; The defined sequence was: -Diagnosis -Planation -Design and documentation -Implementation -Tracking and improvement Once the sequence of implementation was defined and for the development of this work, three of the five stages were covered as indicated below: -Diagnostic: In this stage, a tool was developed and applied to evaluate the fulfillment of the requirements stipulated in the norms NTC-ISO 9001: 2008 and NTC-ISO / IEC 17025: 2005, the methodology of the five forces of Porter and a SWOT matrix was developed. -Planning: Normative and documentary correspondence was developed in order to identify the processes, procedures, documents and records (including technical records) required by the SGI. -Design and documentation: The documentation of the processes and procedure of the Production Laboratory was initiated, this work is carried out by contractors assigned by the Laboratory and by the Process Engineering Unit; the revision of the delivered documents is in charge of the Director of the Production Laboratory, the Process Engineering Unit and the authors of the degree work; In addition to the above, some additional documents required for the implementation of the SGI have been elaborated -The following stages of the implementation sequence will be in charge of the Production Laboratory or the person designated by the laboratory director. Finally, the conclusions and recommendations were established according to what was observed during the development of the degree work.